Evaluasi Tingkat Kerusakan Ruas Jalan Nasional Batas Kab. Kolaka / Kabupaten Bombana – Boepinang Menggunakan Metode Bina Marga - Welendo, La; Nuhun, Ridwan Syah; Apriansyah, Muhammad Risal; Saputra, Wijaya; Muhzamin, Ismail (Innovative: Journal Of Social Science Research, 2024)
Roads allow the mobility of people and goods. As the economy grew and transportation needs increased, more roads were built to connect the wider region. With good road infrastructure, people can travel faster, which supports economic, trade, and social activities. Even so, the maximum function of the road will decrease continuously as time goes by and many large vehicles pass through it. The damage caused by the volume of large vehicles will slowly become one of the causes of transportation activities being hampered. One example of a case raised is the national road section of the Kolaka / Bombana – Boepinang Regency boundary. The purpose of the study is to know what types of damage occurred and the priority scale in repairs on the national road at the Kolaka / Bombana – Boepinang Regency boundary. In this study, a qualitative descriptive method was used in the completion process. The approach used in this study is a quantitative approach. In the Bina Marga method, the level of damage that is of concern when conducting a survey of road damage is cracks, grooves, patches, holes, damage to surfaces and collapse. In the initial stage of the calculation, namely calculating the number of LHR to determine the class value on the road, the LHR value is obtained at 4,575, then determine the road class on the table so that the result is 5. then calculate the number of road damage obtained, namely Crocodile Skin Crack of 0.9%, Longitudinal Crack 0.5%, Patch 2.9%, Hole 0.1%, the result of the calculation of the damage figure obtained a value of 14. So it is necessary to determine the condition of the road based on the table and the value is 5. Determine the priority scale on road conditions. Thus, the condition of the road obtained a priority value of 7, so that when referring to the Regulation of the Directorate General of Binamarga in 1990, it shows that the national road section of the Kolaka / Bombana - Boepinang Regency boundary needs to be categorized in the routine maintenance program.